Reconstruction of the Neopulmonary Root After Coronary Button Harvest for Arterial Switch Operation Using 2-ply Extracellular Matrix (Tyke): A Post-Implant Histology - Bibevski, Steve; Ruzmetov, Mark; Ladich, Elena; Mendoza, Laura E.; Scholl, Frank G. (Frontiers in Cardiovascular Medicine, 2020)
In children with Transposition of the Great Arteries (TGA), the pulmonary artery and aorta are connected to the heart abnormally resulting in blue blood (deoxygenated) recirculating to the body and red blood (oxygenated) recirculating to the lungs. The arterial switch operation (ASO) is the standard of care for transposition of the great arteries (TGA), and given the low risk of early mortality and satisfactory long-term outcomes, focus is now on managing longer term complications such as neo-aortic root dilatation, and pulmonary artery stenosis. Since May 2016, we have used 2-ply extracellular matrix (ECM; Tyke) for reconstruction of the coronary button defects using a pantaloon patch. We present histology of implanted 2-ply ECM (Tyke) from a patient who went back to surgery for development of subaortic stenosis approximately 12 months after ASO.